Pengetahuan Remaja Putri Tentang Konsumsi Tablet FE Pada Saat Menstruasi Pengan Anemia - Angrainy, Rizka; Fitri, Lidia; Wulandari, Vipit (Jurnal Endurance, 2019)
Anemia is a public health problem in the world. According to the World Health Organization (WHO), anemia cases occur 24.8% of the population and an estimated 50-80% of anemia is caused by iron deficiency. Anemia most often occurs in adolescents during menstruation and can be prevented by consuming Fe tablets. Initial survey of 10 female students showed most do not know about consuming Fe tablets during menstruation and 3 of them have Hb below 12 g%. The purpose of research to know the relationship of the adolescent knowledge about consuming fe tablets when menstrual with anemia in Junior High School 20 Pekanbaru 2018. The research design is quantitative Analitic with Cross Sectional approach.The population in this research amounted to 148 people with sampling using technique is purposive sampling as many as 86 people. The data obtained from the questionnaire and Hb measurements on the respondents.The statistical analysis used chi-square. The result of univariate analysis showed that most of the respondents (59,3%) had good knowledge about consuming Fe tablets during menstruation and the majority of respondents (84,3%) is not anemic. Test result obtained P Value < α (0,001<0,05), and it can be concluded that there is a significant relationship between of the adolescent knowledge about consuming Fe tablets when menstrual with anemia.Anemia merupakan masalah kesehatan masyarakat diseluruh dunia. Menurut World Health Organization (WHO), kasus anemia terjadi 24,8% dari populasi dan diperkirakan sekitar 50-80% anemia disebabkan oleh defisiensi besi. Anemia paling sering terjadi pada remaja saat menstruasi dan dapat dicegah dengan mengonsumsi tablet Fe. Survei awal terhadap 10 siswi menunjukkan sebagian besar tidak mengetahui tentang konsumsi tablet Fe pada saat menstruasi dan 3 diantaranya memiliki Hb dibawah 12 gr%. Tujuan penelitian untuk mengetahui hubungan pengetahuan remaja putri tentang  konsumsi tablet Fe pada saat menstruasi dengan anemia di SMP Negeri 20 Pekanbaru. Jenis penelitian Analitik Kuantitatif dengan desain Cross Sectional. Populasi sebanyak 148 orang dengan pengambilan sampel menggunakan purposive sampling sebanyak 86 orang. Data penelitian diperoleh dari kuesioner dan pengukuran Hb. Analisa data menggunakan uji chi-square. Hasil penelitian sebagian besar responden 59,3% memiliki pengetahuan baik tentang mengonsumsi tablet Fe pada saat menstruasi dan mayoritas responden 84,3% tidak anemia. Hasil uji diperoleh Pvalue  < α (0,001<0,05) dan dapat disimpulkan bahwa ada hubungan yang bermakna antara pengetahuan remaja putri tentang konsumsi tablet Fe pada saat menstruasi dengan anemia.